2005
DOI: 10.1096/fj.04-3170fje
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐ulcer drugs promote IgE formation toward dietary antigens in adult patients

Abstract: Recently, we have demonstrated that anti-ulcer drugs, such as H2-receptor blockers and proton pump inhibitors, promote the development of immediate type food allergy toward digestion-labile proteins in mice. The aim of this study was to examine the allergological relevance of these findings in humans. In an observational cohort study, we screened 152 adult patients from a gastroenterological outpatient clinic with negative case histories for atopy or allergy, who were medicated with H2-receptor blockers or pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
138
1
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 206 publications
(151 citation statements)
references
References 35 publications
5
138
1
7
Order By: Relevance
“…Various synthetic antiulcer drugs are currently available, and some of these including RA, are representative histamine H 2 receptor antagonists specifically used to cure gastric ulcers. However, each of these drugs has simple‐to‐severe side effects (Miederer, 1986) including cardiac toxicity (Jakob et al., 2005), risk of pneumonia in hospitalized patients (Mallow et al., 2004), infectious diarrhea (Neal et al., 1994; Ruddell et al., 1980), the development of food allergies (Untersmayr et al., 2005), and thrombocytopenia (Bangia et al., 2011). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various synthetic antiulcer drugs are currently available, and some of these including RA, are representative histamine H 2 receptor antagonists specifically used to cure gastric ulcers. However, each of these drugs has simple‐to‐severe side effects (Miederer, 1986) including cardiac toxicity (Jakob et al., 2005), risk of pneumonia in hospitalized patients (Mallow et al., 2004), infectious diarrhea (Neal et al., 1994; Ruddell et al., 1980), the development of food allergies (Untersmayr et al., 2005), and thrombocytopenia (Bangia et al., 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Although, it is likely to decrease mucosal perfusion in patients with acute renal or cardiac failure, and thereby increases the risk of death (Jakob, Parviainen, Ruokonen, Uusaro, & Takala, 2005). Infectious diarrhea (Neal, Briji, Slack, Hawkey, & Logan, 1994; Ruddell, Axon, Findlay, Bartholomew, & Hill, 1980), developing food allergies (Untersmayr et al., 2005), and thrombocytopenia (Bangia, Kamath, & Mohan, 2011) have also been reported as common side effects of histamine H 2 receptor antagonists (Yesilada & Gurbuz, 2003). In this experiment, RA 100 mg/kg was selected as a positive reference drug to compare the gastric mucosa protective effects based on the previous report (Grover et al., 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The relevance of this mechanism was demonstrated both in the murine system [9][10][11] as well as for humans, as 25% of gastroenterological patients being treated with acid-suppression medication for a 3-month period due to dyspeptic disorders revealed formation of specific IgE antibodies and sensitization towards dietary compounds [9,13].…”
Section: Introductionmentioning
confidence: 99%
“…For the adult population, we could show in previous studies that the risk to develop sensitization against food allergens increases with the usage of acid-suppressing drugs (4,5), which are applied for the treatment of dyspeptic disorders such as gastric reflux, heartburn, and gastritis. We suggested that the hindered peptic digestion due to the elevated pH in the stomach leaves bigger fragments of alimentary proteins.…”
mentioning
confidence: 99%